Investigating the Decline of Fundamental Math Skills Among School Students in Jordan - Bahtiti, Nawal.; Sasa, Tala; Obaidate, Mais; Miri, Omniya; Alfrehat, Rawan (Journal of Posthumanism, 2025)
Mathematics is a foundational subject in global educational curricula, closely linked to advancements in technological and scientific fields. In Jordan, mathematics is taught as a core subject in senior high school to equip students with problem-solving skills. However, many factors contribute to poor mathematics performance among students. This study examines the factors affecting poor mathematics performance and proposes possible policy directions to enhance student performance and improve results in the senior secondary certificate examination. The study sample included 214 students from public and private schools in Irbid city. The findings indicate that poor mathematics performance is primarily associated with ineffective teaching strategies, inadequate procedural approaches, challenging educational environments, and obstacles in following up on study tasks and assignments. These factors collectively impact students’ mastery of fundamental skills and overall academic achievement. We recommend revising the mathematics curriculum focusing on topics that enhance students' ability to apply mathematical knowledge to solve real-world problems.